Distance Protection Algorithm Based Differential Equation - Osal Herrera, William José; García Gracia, Miguel (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>The algorithm of the distance protection based on the differential equation determines the location of a fault in function of the values of the resistance and reactance line that exist in the moment of its occurrence. This algorithm has been tested by investigators with equivalent PI line, being the models line of distributed parameters the most adjusted to the reality. In order to determine the precision of the algorithm in function of the model line considered is carried out the present investigation. The equivalent PI line and models line of distributed parameters is considered. Additionally, the use of digital filters is evaluated. The methodology consists on the simulation of the system of power in the program EMTDC/PSCAD and of the algorithm in the MATLAB to determine its precision and performance limits. A line of transmission of 765 kV is simulated and the results are obtained for single-phase, two-phase and three-phase faults to 10, 50 and 90% of the total longitude of the line. The need of considering an appropriate model of line is demonstrated, and therefore its performance limits, and the improvements that introduce the use of filters